Insights on In Silico Approaches for Identifying Potential Allosteric Modulators from the phytoconstituents of Sida acuta for TNF-α in the Management of Rheumatoid Arthritis (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Tumor necrosis factor-alpha (TNF-α) is a key cytokine in inflammatory and autoimmune diseases, yet the lack of effective oral small-molecule TNF-α inhibitors necessitates alternative therapeutic approaches. This study employs in silico techniques to identify novel TNF-α inhibitors from Sida acuta phytoconstituents. The chemical composition of Sida acuta was collected using literature review, resulting in a library of 45 phytocompounds. Molecular docking studies were conducted to screen these compounds against the allosteric site of TNF-α. Drug-likeness analysis identified three promising candidates: Cryptolepinone, Cryptolepine, and Astragalin. The lead compounds were investigated using steered molecular dynamics (SMD) simulation, followed by molecular dynamics (MD) simulation for 200 ns. The binding affinity of the most promising compound was further evaluated using Molecular Mechanics Poisson–Boltzmann Surface Area (MMPBSA) calculations. The selected compounds exhibited stable interactions within the active pocket of TNF-α. Astragalin demonstrated the highest binding affinity (−7.8 kcal/mol). The identified phytocompounds, particularly Astragalin, hold promise as TNF-α inhibitors. Their stability and strong binding affinity support further investigation for the development of novel therapeutics targeting TNF-α-mediated autoimmune disorders.
Keywords: TNF-α-mediated autoimmune disorders; SMD; TNF-α